PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA MATERI PROGRAM LINEAR UNTUK PESERTA DIDIK KELAS XI SMA/MA - Nur Fauziah; Atma Murni; Maimunah Maimunah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research was conducted due to limited mathematics learning devices that corresponds to The 2013 Curriculum. This research aims to produce learning devices by Problem Based Learning (PBL) model on Linear Program material of class XI. The development model used is 4-D that consist of define, design, develop, and disseminate. The research instrument used is validity device and practicality device. The validity device is a validation sheets to asses the feasibility learning device form syllabus, lesson plan (RPP), and student worksheet (LKPD). The practicality device is practically sheets towards use student worksheets. The learning device developed are validated by three validators. The research trials were conducted in MAN 2 Pekanbaru which is tested in a small group and large group. Based on data analysis, it can be conclude that the average value of syllabus, lesson plan, and student worksheet are 3,62; 3,59; 3,55 that are in very valid category. The student worksheets valued as very practical with mean score for small group and large group testing are 3,51 and 3,49 that are in very practical category. This Research and Development aims to produce learning device by PBL model on Linear Program material of class XI in high school consist of valid syllabus, and lesson plan, and valid too practical for student worksheets.Key Words: Learning Device, Promblem Based Learning Model, 4-D Model